Sequências de DNA: uma nova abordagem para o alinhamento ótimo - Ioste, Aline Rodrigheri (2016)
The objective of this study is to deeply understand the techniques currently used in optimal alignment of DNA sequences, focused on the strengths and limitations of these methods. Analyzing the feasibility of creating a new logical approach able to ensure optimal results , taking into account existing problems in optimal alignment as: (i ) the numerous alignment possibilities of two sequences , ( ii ) the great need for space and memory the machines, ( ii ) processing time to compute the optimal data and (iv ) exponential growth. This study allowed the beginning of the creation of a new logical approach to the global optimum alignment, showing promising results in higher scores with less need for calculations where the mastery of these new techniques can lead to use search of excellent results in the global alignment optimal in large data bases